Natural history of post‐void residual urine volume over 5 years in community‐dwelling older men: The Concord Health and Ageing in Men Project. Issue 3 (20th September 2017) - Noguchi, Naomi; Chan, Lewis; Cumming, Robert G.; Blyth, Fiona M.; Handelsman, David J.; Waite, Louise M.; Le Couteur, David G.; Naganathan, Vasi
Abstract : Aims: To describe the natural history of post‐void residual urine volume (PVR) in community‐dwelling older men. Methods: The Concord Health and Ageing in Men Project involves a representative sample of community‐dwelling men aged 70 and older in a defined geographic area of Sydney, Australia. PVR were measured at baseline and 2‐year and 5‐year follow‐up. The measurements were considered valid when the voided volumes were 150 mL and over. Three‐hundred twenty‐nine men without conditions that are likely to alter PVR (neurological disorders, prostate cancer, and a history of urological treatment) were included in the analyses. Results: Baseline PVR were 0‐49 mL in 183 men, 50‐99 mL in 59 men, 100‐199 mL in 72 men, 200‐399 mL in 11 men, and 400 mL and over in 4 men. Thirteen out of 314 (4%) men with a baseline PVR of 0‐199 mL and 2 out of 11 (18%) men with a baseline PVR of 200‐399 mL had surgery for benign prostate enlargement (BPE) or indwelling catheterization over 5 years compared to three out of four men (75%) with a PVR of 400 mL and over. In all 101 men with a baseline PVR of less than 400 mL who did not receive urological treatment during follow‐up and had valid PVR data for both 2‐year and 5‐year follow‐up, PVR did not exceed 400 mL at either follow‐up time point. Conclusion: Conservative management may be appropriate for most older men with incidentally found elevated PVR of up to 400 mL.